Street Photography Ethics - Hadley, John (Ethical theory and moral practice, 2022)
In this paper I examine the ethics of street photography. I firstly discuss the close-up ‘in-your-face’ style street photography made famous by American photographer, Bruce Gilden. In close-up street photography, the proximity of the camera to the subject and the element of surprise work in tandem to produce a striking and evocative picture. Close-up street photography is shown to be ethically contentious on wellbeing-related and autonomy-related grounds. I next examine the more orthodox ‘respectable distance’ kind of street photography. In orthodox street photography, the photographer positions the camera some distance away from a nonconsenting subject that may or may not be aware a picture is to be taken. The main ethical problem with this form of street photography relates to the subject’s vanity and sense of self. When street photographers produce and publish images without the consent of subjects, they express their own creative freedom at the expense of the subject’s right to editorial control. I discuss the scope and potentially demanding practical implications of a right to editorial control. To conclude, I offer a workable solution to the ethical dilemma facing street photographers and discuss the implications of smart phones and photo-sharing social media platforms.